New orientation of study on economic psychology and behaviour - You Yucong (De Gruyter, 2019)
Economic psychology refers to the impact of psychological factors on economic changes, and its outward manifestation is economic behaviour. Psychology, as a science studying human psychology and behaviour, has no reason to ignore the study of economic activities. This study summarizes the latest research results and conclusions of economic psychology from three aspects of behaviour level, body signal and other people’s movement or displacement. In addition, it expounds the reflection of economic psychology, the reflection of rational human hypothesis of traditional economics and the prospect of future research. From the perspective of economic psychology, it is of great significance to analyse the psychological motivation behind the conflicts and interests in the study of economic psychology and behaviour so as to construct the harmonious behaviour relationship of “psychological contract” on the basis of the rational mechanism of interest distribution.